Students’ Views toward the Usage of Weblogs for Educational Purposes in Nigerian Tertiary Institutions - Oladele Dennis Omodara; Olukayode Solomon Aboderin (RIRAI Publisher, 2022)
The aim of this paper was to evaluate students’ views toward the usage of weblogs for educational purposes in Ondo state tertiary institutions. Three research questions were designed to guide the study. The population consisted of all undergraduates in three selected tertiary institutions in Ondo state. The sample of the study consisted of 358 respondents who were selected using convenience and purposive sampling techniques. A self-structured questionnaire was used to collect data. The result of the findings revealed that students are aware of the usage of weblogs for educational purposes. The findings revealed that students show a positive perception toward the weblog. It was also revealed that Blogs help to provide solutions to Group assignments through enhanced interaction, promote reflective learning, and enhance interaction between teachers and students. Lastly, the results of the study revealed that constraints such as inadequate electricity, bad internet facility, lack of mobile phones and personal computers, lack of relevant software, and insufficient knowledge are the constraints toward the usage of weblogs. Based on the findings of this study, it was recommended among other things that administrators of tertiary institutions should create an enabling environment for intellectual exchange, aligning with tertiary institutions' curriculum to promote the use of weblogs for educational purposes. It was also recommended that Governments should install robust and reliable Internet (Wi-Fi) facilities through the Department of ICT Directorate in the tertiary institutions.